High-performance naphthalene epoxy resins cured by catalyst for packaging materials. (December 2022) - Liu, Jiaming; Liu, Xiaohong; Chen, Bifang; Feng, Zhiqiang; Qin, Jingjing; Wu, Mengqin; Chen, Long; Chen, Xi; Liang, Liyan
Abstract: Epoxy resins are widely used for electronic packaging materials due to their good performance. A common way to cure epoxy is to add anhydride as a hardener, to this, we added a less used curing method, catalytic curing, to study their effect on the curing system and curd samples. Polymers containing naphthalene rings usually have low moisture absorption, good thermal stability, dimensional stability, and dielectric properties. Here, we used two naphthalene epoxy monomers (1, 6- naphthalene diglycidyl ether (1, 6-NDE) and 2, 7-NDE) and cured them with two methods (anhydride (methyl nadic anhydride, MNA) / accelerator (Tris(dimethylaminomethyl)phenol, DMP-30) curing system and catalyst (DMP-30) curing system). We obtained four types of epoxy resins and compared the differences in their structure and performance. All epoxy resins had excellent tensile properties at around 100 MPa tensile strength. Catalyst cured resins had better thermal stability and higher glass transition temperature that close to 180 ˚C (Tg -DMA), compared with anhydride cured resins. Meanwhile, 1, 6-naphthalene epoxy resins had better performance than 2, 7-naphthalene epoxy resins in high glass transition temperature and high crosslink density. Overall, all naphthalene epoxy resins had good performances, and catalyst-cured resins performed better and provided an additional method. Herein, these types of naphthalene epoxy resins have potential applications in the field of electronic packaging. Graphical Abstract: ga1 Highlights: Molecular arrangement inferred from mode layer spacing and crosslink density. Spatial resistance affects the cross-linking density and the performance of the resins. Better thermal stability and solvent resistance of catalyst cured resins.